2016
DOI: 10.1007/s11060-016-2056-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antiepileptic drugs on the growth of glioblastoma cell lines

Abstract: To determine the effects of antiepileptic drug compounds on glioblastoma cellular growth, we exposed glioblastoma cell lines to select antiepileptic drugs. The effects of selected antiepileptic drugs on glioblastoma cells were measured by MTT assay. For compounds showing significant inhibition, cell cycle analysis was performed. Statistical analysis was performed using SPSS. The antiepileptic compounds selected for screening included carbamazepine, ethosuximide, gabapentin, lamotrigine, levetiracetam, magnesiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
2
27
0
2
Order By: Relevance
“…However, 24-hour exposure to OXC and STR did not significantly alter [ 3 H]-folic acid uptake per protein, compared to the control (Table 4). OXC was shown to reduce the viability of hippocampal neurons (Morte et al, 2013), glioblastoma (Lee et al, 2016), and several cancer cell lines, such as MCF-7, HeLa, and HepG2 cells (El Sharkawi et al, 2014). The present study suggests that administration of OXC and STR during pregnancy may affect the placental development.…”
Section: As Shown Insupporting
confidence: 51%
“…However, 24-hour exposure to OXC and STR did not significantly alter [ 3 H]-folic acid uptake per protein, compared to the control (Table 4). OXC was shown to reduce the viability of hippocampal neurons (Morte et al, 2013), glioblastoma (Lee et al, 2016), and several cancer cell lines, such as MCF-7, HeLa, and HepG2 cells (El Sharkawi et al, 2014). The present study suggests that administration of OXC and STR during pregnancy may affect the placental development.…”
Section: As Shown Insupporting
confidence: 51%
“…When we evaluated the ability of topiramate to inhibit GBM growth in the presence or absence of TMZ, we noted no additional benefit (Supplemental Figure 3), but a recent study indicated that topiramate treatment decreased intracellular pH in U87 GBM cells in vivo (47). Antiepileptic drugs including topiramate are often used for treatment of tumor-associated epilepsy, but results to determine direct efficacy against GBM cell growth in vitro have been mixed (48,49). Although several antiepileptic drugs have not demonstrated significant improvements in overall survival (50), our data suggest that further clinical evaluation of those with carbonic anhydrase inhibitor function is warranted.…”
Section: Discussionmentioning
confidence: 96%
“…These three groups includes drugs that carry out their action by blocking neuronal ion channels, the other group of drugs carry out their function by facilitating gamma-aminobutryic action [3]. The last group carries out their function in a mode that has not been resolved yet.…”
Section: Anti Epileptic Medicines and How They Stop Or Slow Down Tumomentioning
confidence: 99%
“…Phenobarbitals have also been associated with lung cancer in humans and this is in early epidemiological studies. They have also been implicated in the occurrence of brain tumours [3]. The other commonly used group of anti epileptic drugs are the phenytoin.…”
Section: Anti Epileptic Medicines and How They Stop Or Slow Down Tumomentioning
confidence: 99%
See 1 more Smart Citation